ANALISIS PERENCANAAN AGREGAT PADA CV. SUMBER REZEKI DI SAMARINDA - -, Dede Mariyani (EKONOMIA, 2014)
This study on the CV. Sumber Rezeki is one company whose main activity is the manufacture of tile . Tile that is used as one important component in the settlement , this time has been much needed by the consumer .            Plus the development of business - residential construction or real estate settlement which means activity is also increasing use of tile . Therefore CV. Sumber Rezeki always trying to improve its business in accordance with the pace and level of development today to meet market demand .            Based on the above , it can be a problem in this study is : " Is the aggregate planning strategies were applied to CV. Sumber Rezeki able to minimize the extra cost ? " .            The purpose of this study was to determine the aggregate planning and implementation to determine the application of the aggregate planning strategies on CV. Sumber Rezeki in Samarinda .            The analytical tool used in this research is a method of calculating the cost of a table is an additional source of sustenance CV and compare it with the basic concept of using the formula relevan.dan incremental cost ( Additional Cost ) = Cost + Labor Cost + Cost Lembuh Else.            Based on the research and analysis conducted turned out aggregate planning strategies were implemented, CV. Sumber Rezeki fortunes have not been able to minimize additional costs